Pengaruh Motivasi Karir Terhadap Pemilihan Program Studi Akuntansi - Arum Ardianingsih (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Motivation is the main driver for a person to be more so in taking a decision. Career is well established that the desired level of work for many people. Career motivation encourage someone to choose accounting study program for career opportunities on offer for accounting graduates broaderand includes five professions are accountant educators, public sector accountants, management accountants, public accountants and tax accountants. This study aims to provide empirical evidence that motivation influence on decision-making career choosing accounting study program. The study was conducted by using the classical assumption test and simple regression analysis. The results showed that the career motivation significantly influence decision making selecting accounting studyprogram with positive research directions.Keywords: Accounting study program, Career Motivation, university.